Analisis Dan Perancangan Manajemen Bandwith Menggunakan Metode Hierarchial Token Bucket (HTB) Dan Filtering Layer7 Protocol Mikrotik - Khaidir, Muhammad; Noor, Muhammad Fajrian (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Internet users often complain about unstable internet connections and insufficient bandwidth, in fact the main problem is not because of insufficient bandwidth, but because there is no bandwidth management that regulates which packages are important and need to be prioritized. The research entitled "Analysis and Design of Bandwith Management uses Hierarchial Token Bucket (HTB) Method and Filtering uses Layer7 Protocol in Candi Agung Student Dormitory Hostpot Network", has the formulation of the problem of bandwidth management performance using the Hierarchial Token Bucket (HTB) method in terms of Quality of Service (QoS) with Throughput, Delay, Jitter and Packet Loss parameters. The purpose of this study is to analyze and design bandwidth management using the Hierarchial Token Bucket (HTB) method and limit the bandwidth of video streaming youtube.com using the Layer7 Protocol mikrotik feature in Candi Agung Student Dormitory Hostpot Network. The method used in network design and development in this study is the PPDIOO method which includes Prepare, Plan, Design, Implement, Operate and Optimize. This research produces a bandwidth management system that can provide guaranteed bandwidth to every active user according to the user's priority and package even though the internet connection is busy. It aims to maintain internet access can be used according to the needs of all users.